Extemporaneous suspensions in the scheme of complex therapy of dermatological skin diseases - Zujkina, Svitlana; Nataliya, Shtuchna (Annals of Mechnikov’s Institute, 2022)
The relevance of the study of acne (Acne vulgaris) depends on its significant prevalence among young and middle-aged people and the chronic course of the disease, resistance to conventional therapy, and impaired psycho-emotional status and social adaptation in patients. Acne affects 9.4 % of the world’s population. Therefore, this disease remains one of the most common problems in the practice of dermatologists and cosmetologists. In 64 and 43 % of people, acne persists until the age of 20-30, respectively, and suicidal thoughts are more common in those with severe forms of acne than with mild ones. In the United States, the cost of acne in terms of treatment and productivity loss is over 3 billion per year. The aim of the work was to study the prospects for the use of extemporaneous remedies in the form of suspensions for external use in the scheme of complex acne treatment. In the aspect of the researched problem, the materials of State Register of Medicinal Products of Ukraine, Protocol on the provision of medical assistance to patients with vulgar acne, Addendum to the order of the Ministry of Health No. 312 of 08-05-2009, the provisions of the guidelines of the American Academy of Dermatology on the treatment of patients with acne vulgaris and the Guidelines for the treatment of patients with acne vulgaris within the limits of primary and specialized medical care (Great Britain) were studied. Using pharmacotechnological methods, technology was developed and quality indicators of several extemporaneous suspensions for complex pharmacocorrection of acne were investigated. Key words: aсne, drugs, extemporaneous suspension.